Ensinando crianças autistas a requisitar: avaliação da aquisição e generalização de comunicação mediada por figuras com uso do PECS - Juliana Campos de Jesus (2013)
Autism is characterized by severe and pervasive damage in threeareas of development such as: social interaction, communication and the presence of stereotyped behaviors, interests and activities. Taking into consideration that 30 to 50% of those affected by the disorder do not develop any natural speech, interventions with the purpose of developing a functional communication should be a priority in the treatment of autistic children. The purpose of this dissertation wasto promote the acquisition and investigate the generalization of mands by autistic children whowere taught the first three phases of the Picture Exchange Communication System (PECS). The study included four children diagnosed with autism who were chosen to take part in the research because they presented significant deficits in verbal performance. The study implemented PECS to teach responses to mands in a system of exchanging cards with photographic representations with reinforcing stimuli. We recorded the responses to mands during and after the intervention in two different environments (home and school). The results showed that the intervention was effective in promoting the acquisitionand generalization mands at home for three participants.Various procedure aspects are discuss to explain failure to observe generalization at school.